ANALISIS KEDISIPILNAN PENDIDIK - Zulaehatus Sofiyah (TANZHIMUNA : Jurnal Manajemen Pendidikan Islam, 2023)
The purpose of this study was to determine the discipline of Teachers and solutions to overcome the lack of discipline of Teachers at MTs Tanbihul Ghofiilin. The method used is descriptive qualitative with saturated samples for Teachers and Probability Sampling for student samples. The results of the questionnaire distributed were interpreted using a 4-level Liket scale. This study found that the discipline of Teachers at MTs Tanbihul Ghofilin Mantrianom Banjarnegara when in class was categorized as good. The results of the evaluation data show a very good category. This means that Teachers conduct evaluations very well and follow every process of evaluation. Solutions offered by looking at previous research supervision, motivation, culture built from the principal as well as punishment and rewards increase the discipline of Teachers